(untitled) (Research, Society and Development, 2022)
The objective of the study is the resistance coefficients in metallic structures in fire situation. The coefficients are in everything we can imagine, from the simple walk to work every day to the incredible and systematic production of heavy machinery for the industry. There are several factors that determine the lows and highs of being late or early to work, or the bankruptcy or profits of companies. Safety factors are also included, but in proportion format and, according to the variability of a given body of study, it will be possible to define whether it will have an increase or decrease in its degree of safety and precision from theoretical to real. In metallic structures, the metal itself has a great disadvantage when it has high temperatures as an aggressor. Metallic materials have a good density, but this same density, as it is a metallic material, suffers from an increase in the high vibration of the internal particles, causing the metallic material to lose cohesion and begin to feel natural plastic deformations and, roughly speaking, become "soft". The metallic profile has a low compressive strength and, if the part still has high slenderness, it will have this fragility at least doubled, having fragile flexural strength due to the influence of slenderness. The coefficients will be treated as fillers to fill the holes caused by the resistance deficiency of the metallic component and can be portrayed either as an increase in the cross section of the metallic element or as a support structure as protection of materials against fire.